Pre-eclampsia: the outcome of term pregnancies at Rahima Moosa Mother and Child Hospital - Naidoo, Kumesha (My University, 2015)
Background Pre-eclampsia and its complications remain a significant cause of maternal and perinatal morbidity and mortality on a global level. There are few data regarding the maternal and fetal outcome of pre-eclampsia at term. Studies suggest that poor maternal outcome is more prevalent as one approaches term, while there are conflicting findings regarding the outcomes of the babies born to term pre-eclamptic patients. Objective To determine the prevalence of pre-eclampsia in term pregnancies at Rahima Moosa Mother and Child Hospital (RMMCH), a hospital that provides district and higher level referral services, and to assess the severity of maternal disease in pre-eclampsia at term, as well as fetal outcomes. Methods This was a prospective cross-sectional, descriptive study on women giving birth at term with pre-eclampsia. All women were followed up until delivery. The indication for and mode of delivery, maternal progress and complications, as well as fetal outcome, were recorded. Results Seventy-eight patients were entered into the study, giving a hospital prevalence rate of pre-eclampsia at term of 1.2%. The major maternal complications were those of severe hypertension (75.6%), eclampsia (9%), HELLP syndrome (3.8%), and pulmonary oedema (7.7%). There was one maternal death. Fifty-one patients (65%) delivered by caesarean section. Major fetal complications encountered were respiratory distress (7.5%) and birth asphyxia (3.7%). There was one neonatal death from meconium aspiration.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology MMed(O&G) Johannesburg, April 2015
Keywords: Pregnancy; Pre-Eclampsia